The Concept of Extradition. Procedural-Criminal Aspects - Vizdoaga, Tatiana; Tsonku , Sanda (Acta Universitatis Danubius. Administratio, 2022)
Extradition is an act of interstate legal assistance in criminal matters that pursues the purpose of transferring a person who is under criminal investigation or is criminally convicted from the area of judicial sovereignty of one state to the area of the other state. Extradition can be characterized by the following features: a) relations between two states, one of which is the applicant, the other the requested; b) all issues related to extradition fall within the competence of the states that have national legal provisions on extradition, are party to international treaties in this field and carry out practical work on extradition issues; c) the subject of extradition is a natural person, who is outside the territory of the state requesting extradition; d) extradition can only take place after the commission of a crime that gives grounds for extradition, violations that attract contravention or civil liability cannot serve as grounds for requesting the extradition of a person; e) extradition assumes that the extradited person is an accused, defendant or a convicted person.